Self-regulated learning and academic achievement in Malaysian undergraduates - Mohd. Kosnin, Azlina (Shannon Research Press, 2007)

(untitled)
This study is an investigation of the ability of self-regulated learning (SRL) as measured by the Motivated Strategies for Learning Questionnaires (MSLQ) to predict academic achievement among undergraduates in Malaysia. A total of 460 second-year engineering undergraduates from the Universiti Teknologi Malaysia participated in the study. Academic achievement was measured by the students’ grade point average. The results show that the MSLQ is a reliable tool and SRL is a significant predictor of Malaysian undergraduates’ academic achievement. Significant relationships between SRL and academic achievement were found, nevertheless differences in the composition of significant predictor sub-scales are also found between achievement groups.